A hesperetin derivative plays a role in immunoregulatory effect on human macrophages - Ma, Jian-li; Li, Chun (Cellular and Molecular Biology, 2019)
The immune system is an important physiological defense system. Its balance and stability are closely related to the body’s health. Once the immune system loses its dynamic balance, the immune response will be blocked, which will lead to the occurrence of various diseases. Hesperetin is a kind of natural flavonoids extracted from citrus fruits of Rutaceae and it has many pharmacological activities. However, its water solubility and liposolubility are poor, and it is easy to be quickly metabolized in vivo, so it is difficult to maintain high blood drug concentration. Therefore, its derivative (HES) was found by structural modification. In this study, THP-1 cells were used as experimental model to investigate the immunomodulatory effect of HES in vitro. The results showed that HES participates in immune response by enhancing phagocytosis of macrophages to promote the release of NO, IL-6 and IL-1Î², and enhancing immunity by up-regulating the expression of Bcl-2 and Bcl-XL proteins. This study provides a theoretical and practical basis for the development of HES as an immunomodulator in the future.